PERKEMBANGAN KEDUDUKAN PEREMPUAN DALAM HUKUM ADBALI (Studi di Kota Denpasar) - Sukerti, Ni Nyoman (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
Women as citizens of the ancients is still received discriminatory treatment in some aspects of life, although the government has made some rules that provide protection to women evens have ratified CEDAW. The Constitution also been set in Article 27, paragraphs 1 and 2, but discrimination against women still exist, especially in the traditional law of Bali inheritance. On the basis of the two problems posed namely 1). Against wealth whose position daughter suffered developments in traditional law of Bali heritance? and, 2). What factors influence the occurrence of the development of women position in traditional law of Bali heritance ? Results of the research showed that inherited asset is generally daughter disposable property rich guna kaya. Varied forms of inherited property have fixed things as well as moving objects. Rights received largely daughter also vary greatly between the cases of the other cases, this depends of the economic condition of her parents. Daughter of position heirs are not burdened family responsibilities. So, the position of the daughter of experience in the development of traditional law of Bali heritance limited -use property rich guna kaya . Factors that influence the occurrence of the development of women position in traditional law of Bali heritance, the availability of legislation that gender perspective, there is a paradigm shift in attitude and behavior of the parents of the girls looked, viability of public education level and economy growing family.
Keywords: development; the position of women; traditional law of Bali heritance